Postdecisional Processing Delays in Metacognitive Monitoring After Traumatic Brain Injury. Issue 2 (March 2020) - Chiou, Kathy S.; Genova, Helen M.; Lengenfelder, Jean; Chiaravalloti, Nancy D.
Abstract : Objective: To document the process by which metacognitive judgments ("online" monitoring of one's own cognitive performance during task completion) are made after traumatic brain injury (TBI). Participants: Sixteen community-dwelling adults with moderate to severe TBI and 16 matched healthy controls. Design: Prospective, cross-sectional design. Measures: Metacognitive retrospective confidence judgments and reaction times were collected as participants performed a metamemory task. Results: Adults with TBI did not differ from healthy peers in metacognitive accuracy; however, they took significantly longer to make retrospective confidence judgments. Retrospective confidence judgment reaction times were not consistently correlated to measures of processing speed in either sample. Conclusions: Adults with TBI engage in different postdecisional processes to make metacognitive judgments compared with healthy controls. Findings suggest that reaction times may be an important dimension of metacognition to assess clinically after TBI.